Dampak Alih Fungsi Lahan Sawah Bagi Perkembangan Infrastruktur Wilayah di Kota Padang Tahun 2010-2020 - Rizka Syahyeni; Elvi Zuriyani; Rika Despica (Journal on Education, 2023)
This study aims to determine: (1) To find out the shape of the area of ​​change in the conversion of paddy fields to infrastructure in the city of Padang. (2) To find out the impact of paddy field conversion on infrastructure in the city of Padang. This type of research is a descriptive quantitative approach. The population in this study is all sub-districts in the city of Padang, while the samples in this study are the Kuranji sub-district and the Pauh sub-district. The sampling technique in this study was purposive random sampling. Data analysis technique used spatial overlay analysis technique using ArcGIS and descriptive analysis technique using a questionnaire. Research result. (1) The area of ​​conversion of paddy fields to infrastructure in Padang City, namely settlements in Kuranji District, is 567.1 ha. The area of ​​change in paddy fields in Padang City in 2010-2020 is 1,315.81 ha. (2) The impact of the conversion of paddy fields to infrastructure, namely roads, bridges, schools, water resources and settlements. a) Roads with a percentage of 100% are construction of new roads. b) Bridges with a percentage of 64.3% where no bridges are built. c) Schools with a percentage of 67% do not have SD, SMP and SMA construction. d) Water Resources with a percentage of 75.16% reduced water resources. e) Settlements with an overall percentage of 100% have been built with many new settlements and the population has increased.